2013
DOI: 10.2298/gsgd1304001m
|View full text |Cite
|
Sign up to set email alerts
|

Eolian relief of southeast Banatian

Abstract: During the Quaternary, eolian processes had dominantly morphological importance in shaping of southeastern Banat. In morphology of this region, therefore, dominates loess plains, Zagajica's ridge and Deliblato and Banatian dune field. About the genesis of loess plains, Zagajica's ridge and Deliblato dune field are different, very often opposite opinions. Meanwhile, during the geomorphologic mapping of Vojvodina, at the end of nineties years of last century and at the beginning of 21st century… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Wing lengths can reach up to 1.5 km and have heights of ca. 5-10 m (Menković, 2013). The dunes have formed under significant vegetative control and with a moderate sand supply, and are dated to the Early Holocene (Sipos et al, 2016).…”
Section: Proxy Wind Data From Loess and Dunesmentioning
confidence: 99%
“…Wing lengths can reach up to 1.5 km and have heights of ca. 5-10 m (Menković, 2013). The dunes have formed under significant vegetative control and with a moderate sand supply, and are dated to the Early Holocene (Sipos et al, 2016).…”
Section: Proxy Wind Data From Loess and Dunesmentioning
confidence: 99%
“…Between the loess plateaus, there is a Vršac-Alibunar tectonic depression (Figure 3A). In this depression and the river valleys that are open to it, the Upper Pleistocene river terrace was built (Figure 3A), by mixing marsh sediments and loess blown from the surrounding plateaus [55].…”
Section: Geomorphological Settingmentioning
confidence: 99%
“…The Banatska peščara Sands is characterized by a distinctly dune relief, which represents the long dunes of the NW-SE direction and the interdepression [47]. The height difference between dunes and depressions is 20-30 m. The sand accumulated in the Banatska peščara sands comes from the alluvial material made by the Danube floods during the Holocene [55]. This sand is mostly driven by prevailing winds that blow from the SE quadrant (Košava wind) and form more than 1300 parabolic dunes [58].…”
Section: Geomorphological Settingmentioning
confidence: 99%
“…There is minimal information concerning blown sand movement in the Deliblato Sands in Serbia, an area termed the 'Desert of Europe' or 'European Sahara,' because it is characterized by large, fixed dune forms that were bare in the past few centuries, and provided a desert-like look to the landscape until the beginning of the 20 th century (Cholnoky, 1902). The development of the dune field has been investigated by several researchers in the past, and primarily based on geomorphic observations, various hypotheses and assumptions were made concerning the origin and the time of its formation (Cholnoky, 1910(Cholnoky, , 1940Menković, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…As the sand overlies loess at some locations, other authors placed the major deflation phase in the Holocene, subsequent to fluvial deposition and loess formation (Marković-Marjanovič, 1950). More recently, Menković (2013) concluded that the sand sheet was formed during the last glacial termination and the Preboreal (10.3–9 ka) and Boreal (9–8 ka) periods of the Early Holocene (Greenlandian stage), and, after an Atlantic period (8–5 ka) stabilization in the Mid Holocene (Northgrippian stage), the present-day dunes developed in the Subboreal period (5–2.5 ka) and later (Meghalayan stage). Nevertheless, it is essential to underline that no numeric age data were available when these hypotheses were formulated.…”
Section: Introductionmentioning
confidence: 99%